Estimation of thigh muscle volume by multi-frequency bioelectrical impedance - Komiya, H.; Tsubakihara, M. (Advances in Exercise and Sports Physiology, 2012)
The aim of this study was to evaluate the validity of estimating thigh muscle volume using multi-frequency bioelectrical impedance analysis (BIA). Two methods of measuring muscle volume were used, and the frequency range was varied from 4 kHz to 1024 kHz. In the first method, the thigh was divided into three parts-proximal, central and distal and each volume was totaled. In the second method, the volume of the whole thigh was measured as one cylindrical conductor. The optimal frequencies for measuring the muscle volume and measurement method were examined. Ten healthy male soccer players (age 20.1 +/- 1.0 yr) were enrolled in the study. They underwent magnetic resonance imaging (MRI) to assess thigh muscle volume and their anthropometry parameters, and BIA were measured. Thigh muscle volume obtained by MRI was used as a dependent variable, and multiple regression analysis was performed by using anthropometry values, age, BMI, impedance, and impedance index (IPI) as independent variables. The following equation was used for estimating total muscle volume (TV) using IPI.: TV=Lx16.81 + Cx146.37 + ZI (50 kHz) x 74.78-|4859.06 where, TV is whole muscle volume; L is length of thigh; and C is circumference around the thigh; ZI (50 kHz) means IPI at 50 kHz. The correlation of TV observed by MRI and TV estimated by the equation using IPI was r = 0.911 (p < 0.001). The frequency of 50 kHz showed the best performance in this study. Estimation of thigh muscle volume using the multi-frequency BIA method has high reliability, and is suggested to be an effective and simple measurement method for estimating muscle volume.